A critical analysis of the use of fair value by Islamic Financial Institutions. Issue 2 (11th April 2016) - Gharbi, Leila
Abstract : Purpose: This paper aims to address a specific question over the compatibility of International Financial Reporting Standards with Islamic finance regarding the use of interest rate as discounting rate in impairment testing and valuation techniques. Design/methodology/approach: Inductive methodology and qualitative-narrative methods are used to explore the available texts and literature. Findings: There are two main findings: first, the use of reference rate obtained in non-Islamic financial system is inappropriate from the Islamic perspective. Interest-based valuation techniques have not been adopted by the Accounting and Auditing Organization for Islamic Financial Institutions in its adaptation of conventional accounting practices, and the majority of Islamic scholars argue against Interest rate benchmarking. Second, the authors suggest nominal gross domestic product (NGDP) growth rate as an alternative benchmark because Islamic finance, in its ideal sense, is based on and closely linked to the real sector. Moreover, recent studies show that there are no statistical differences between NGDP growth rate and nominal interest rate for most of the countries studied. Originality/value: This paper highlights the accounting implications of the prohibition of interest for valuation techniques and raises the need of acceptable alternative pricing benchmark.